SUPERVISION OF EDUCATION IN THE QUR'AN PERSPECTIVE (AN ANALYSIS OF TAFSIR TAHLILI QS. AL-HUJURAT VERSE 6 IN THE STUDY OF ISLAMIC EDUCATION MANAGEMENT) - Adi Ansari (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2022)
This study aims to explore the concept of educational supervision from the perspective of the Qur'an. The Qur'an is a holy book, a source of law and a way of life for Muslims until the Day of Judgment. As long as Muslims adhere to the Qur'an in living their lives, they will be safe in this world and in the hereafter. This type of research is library research with the tahlili interpretation method to interpret the verses of the Qur'an which are used as a reference for theoretical principles in the study of Islamic education management. This study found one verse that inspired the principle of supervision of educators and education personnel, namely QS. Al Hujuraat/49 verse 6. The conclusion of this research is, this verse is a source of principle for leaders in Islamic educational institutions to be really careful in supervising their subordinates or educators and education staff by responding to the truth of information or news and may not based on prejudice and evil intentions so that ultimately the actions taken can cause harm to others. The implications of the principle of this verse are very large for leaders in Islamic educational institutions in particular and educational institutions in general, accuracy in evaluating information on news is very important because there are so many problems that come and go every day. The bigger an educational institution is, the more complex these problems will be and if these problems are not evaluated jointly in a meeting or meeting of the head of the madrasa/school then the problems will be more numerous and piled up. So with a careful way of supervision or the term tabayyun, all these problems can be solved.